Empowering Tawangmangu Community in Digital Economy: Legal Literacy regarding Peer-to-Peer Lending in the Perspectives of Criminal Law and Private Law - Maradona; Kurniawan, Faizal; Sapta Aprilianto; Agustin, Erni; Amalia, Rizky; Brouwer, Darryl Evan (Jurnal Dedikasi Hukum, 2023)
Financial technology has become an inseparable part of people’s life activities. As technology advances, financial technology makes it easy for people to get instant cash loans to fulfil their needs in life, known as the peer-to-peer lending concept. In Indonesia, this concept is known as Information Technology-Based Joint Funding Services. In practice, the implementation of peer-to-peer lending is often confused by the implementation of online loans that are not registered and do not have any permission from the Financial Services Authority. Various problems arise from the existence of illegal online loans, for example, very high interest rates and collections with pressure and intimidation, which can bring losses to the debtor. This encourages the need for community empowerment activities in Tawangmangu Subdistrict, Karanganyar Regency, Central Java Province regarding the legal aspects of information technology-based joint funding services so as to avoid legal problems related to such lending and borrowing methods. This community service aims to provide insight and increase community literacy to increase the community’s ability to understand the various risks and efforts that can be taken regarding problems arising from online loans. The method used is socialisation and consultation on the problems faced. The results obtained from this activity include increased public knowledge and solutions to the problems faced. Abstrak Pemberdayaan Masyarakat Tawangmangu dalam Ekonomi Digital: Literasi Hukum tentang Peer-to-Peer Lending dalam Perspektif Hukum Pidana dan Hukum Perdata. Financial technology telah menjadi bagian yang tidak terpisahkan dari aktivitas kehidupan masyarakat. Sebagai teknologi, financial technology memberikan kemudahan bagi masyarakat untuk mendapatkan pinjaman dana instan dalam rangka memenuhi kepentingan dalam kehidupannya yang dikenal dengan konsep peer to peer lending. Di Indonesia, konsep ini dikenal dengan nama Layanan Pendanaan Bersama Berbasis Teknologi Informasi. Dalam praktiknya, penyelenggaraan peer to peer landing seringkali menjadi rancu dengan adanya penyelenggaraan pinjaman online yang tidak terdaftar dan tidak memiliki izin dari Otoritas Jasa Keuangan. Berbagai masalah yang timbul dari adanya Pinjaman Online illegal misalnya bunga sangat tinggi maupun penagihan yang disertai tekanan danintimidasi yang dapat membawa kerugian bagi masyarakat. Hal ini mendorong diperlukannya kegiatan pemberdayaan masyarakat Kecamatan Tawangmangu, Kabupaten Karanganyar, Propinsi Jawa Tengah mengenai aspek hukum Layanan Pendanaan Bersama Berbasis Teknologi Informasi sehingga terhindar dari masalah hukum yang berkaitan dengan metode pinjam meminjam seperti itu. Pengabdian kepada Masyarakat ini bertujuan untuk memberikan wawasan dan peningkatan literasi masyarakat untuk meningkatkan kemampuan masyarakat memahami berbagai risiko dan upaya yang dapat dilakukan terkait permasalahan yang timbul dari pinjaman online. Metode yang digunakan adalah sosialisasi dan konsultasi permasalahan yang dihadapi. Hasil yang diperoleh dari kegiatan ini adalah meningkatnya pengetahuan masyarakat dan solusi atas permasalahan yang dihadapi.